Pedagogies of the Unimpressed: Re-Educating Ontario Women for the Modern Energy Regime, 1900-1940 - Sandwell, Ruth (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
In the early decades of the twentieth century, Ontario homemakers were targets of a multi-faceted educational campaign in which a range of corporate and social reform groups sought to change the ways women cooked, cleaned and heated their homes. This article explores these highly gendered pedagogies of modernity and resituates them within the context of Canadian energy history, focusing on household electrification to highlight Ontario women’s resistance, in terms of their day-to-day household practices, to this educational campaign. It argues that women remained largely unimpressed by the promise of electrification into the 1940s, not only because of the problems inherent in the new, centralized supply of energy itself, but because of the deeply gendered cultural practices and preferences that continued to define women’s life and work within the older energy regime of the Ontario home.